RATAN-600 and RadioAstron reveal the neutrino-associated blazar TXS 0506+056 as a typical variable AGN. Issue 2 (15th January 2020) - Kovalev, Yu.A.; Kardashev, N.S.; Kovalev, Y.Y.; Sokolovsky, K.V.; Voitsik, P.A.; Edwards, P.G.; Popkov, A.V.; Zhekanis, G.V.; Sotnikova, Yu.V.; Nizhelsky, N.A.; Tsybulev, P.G.; Erkenov, A.K.; et al.
Abstract: The possible association with the high-energy neutrino event IceCube-170922A has sparked interest in the blazar TXS 0506+056. We present 72 instantaneous 1–22 GHz spectra measured over the past 20 years with the RATAN-600 telescope and compare them with the results of observations of 700 variable Active Galactic Nuclei (AGN) studied within the same program. The recent radio flare of TXS 0506+056 started from a minimum in 2013 and reached its first peak in December 2017 and a second peak in May-June 2018. This was the third strong radio flare in this source since 1997. The spectrum remains nearly flat during the flares. The spectral shape and variability pattern observed in TXS 0506+056 are typical for variable AGN. RadioAstron Space VLBI observations in 2013–2015 did not detect TXS 0506+056 on space-ground baselines of more than 9 Earth diameters. However, an observation on 23 September 2015 resulted in the detection of interferometric signal on 6 Earth diameter baselines at 18 cm close to the detection limit. We consider the possibility that TXS 0506+056 and other AGN may accelerate relativistic protons more efficiently than electrons. Relativistic protons are necessary to produce both the high-energy neutrinos observed in the IceCube Observatory and the high AGN brightness temperatures implied by the RadioAstron detection. They may also provide the main contribution to the observed synchrotron radiation of parsec-scale AGN jets. This supports the suggestion that relativistic protons may play a much more important part in extragalactic astrophysics than earlier anticipated.